Liana abundance, tree crown infestation, and tree regeneration ten years after liana cutting in a subtropical forest - Campanello, Paula Inés (2012)
Liana abundance and host tree colonization dynamics during a 10-year period were studied in a subtropical Atlantic Forest in Northeastern Argentina. The impact of liana and woody bamboo cutting on liana abundance and diversity, tree infestation and advanced tree regeneration (individuals 5 cm and 10 cm DBH) was assessed during the same time period. Six permanent 1 ha plots (three control and three cutting plots) were located in the year 2000 in a native forest stand. Three plots were subjected to bamboo and liana cutting (BLC) and other three left as control (C). All lianas regardless of their diameters were cut. Liana abundance and basal area increased more than 50% after ten years in C plots, while the proportion of trees infested with lianas increased from 69% in 2000 to 83% in 2010 in the same plots. In this time period some trees species were able to shed their lianas but increased liana load was observed in other tree species which accounted for the increased proportion of infested trees. In BLC plots the proportion of infested trees was similar (about 60%) in 2000 and 2010, indicating a rapid liana colonization of trees after the treatment. Trees with short branch-free boles were rapidly re-infested compared to taller trees. Liana abundance and basal area were substantially lower in BLC compared to C plots, consistent with the relatively short period of colonization in the cutting plots. Tendriled lianas decreased more than twiners and scramblers. Liana richness and species evenness was not affected by the cutting treatment. Advance tree regeneration was partially affected: tree sapling abundance was similar between C and BLC plots but tree basal area was slightly lower in 2010 in C plots indicating that the treatment enhanced sapling growth. No differences in liana infestation on tree saplings were found between C and BLC plots in 2010. Our results indicate a rapid recovery of lianas after cutting, particularly for individuals smaller than 2.5 cm DBH, and a substantial effect of this silvicultural treatment applied to enhance tree regeneration. Similar to other tropical forests, a relatively large increase in liana abundance and tree infestation, as observed in C plots, is occurring in this semideciduous forest.